Some Useful Aspects Of Fuzzy Operations And Systems Including OWA With A Couple Of Extensions To Type-2 Fuzzy Systems - Chandramohan, Aarthi (2008)
This thesis elucidates novel and different definitions for fuzzy set operations, hedges, rule reduction techniques and defuzzification methods with some extensions to type-2 fuzzy systems.